Oleandrin: A Systematic Review of its Natural Sources, Structural Properties, Detection Methods, Pharmacokinetics and Toxicology - Zhai, Jinxiao; Dong, Xiaoru; Yan, Fenglian; Guo, Hongsong; Yang, Jinling (Frontiers in Pharmacology, 2022)
Oleandrin is a highly lipid-soluble cardiac glycoside isolated from the plant Nerium oleander (Apocynaceae) and is used as a traditional herbal medicine due to its excellent pharmacological properties. It is widely applied for various disease treatments, such as congestive heart failure. Recently, oleandrin has attracted widespread attention due to its extensive anti-cancer and novel anti-viral effects. However, oleandrin has a narrow therapeutic window and exhibits various toxicities, especially typical cardiotoxicity, which is often fatal. This severe toxicity and low polarity have significantly hindered its application in the clinic. This review describes natural source, structural properties, and detection methods of oleandrin. Based on reported poisoning cases and sporadic animal experiments, the pharmacokinetic characteristics of oleandrin are summarized, so as to infer some possible phenomena, such as enterohepatic circulation. Moreover, the relevant factors affecting the pharmacokinetics of oleandrin are analyzed, and some research approaches that may ameliorate the pharmacokinetic behavior of oleandrin are proposed. With the toxicology of oleandrin being thoroughly reviewed, the development of safe clinical applications of oleandrin may be possible given potential research strategies to decrease toxicity.